ANALISIS PENGARUH KETEBALAN SHIM TERHADAP PERUBAHAN TEKANAN PENGABUTAN NOZZLE TIPE SATU LUBANG PADA ISUZU PANTHER - Amin Nur Akhmadi; M Taufik Qurohman (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2017)
The development of technology increased rapidly. As a result of the rapid development, there will be a wide variety of technology design, especially in the field of automotive engines. Therefore it needs research and analyzes of the shim thickness variation in the injection pressure, carburetion and carburation trail that produced. Motor vehicle Emission exhaust gas contains harmful pollutant to human and the environment, the pollutant which is produced such as carbon monoxide, hydrocarbons, nitrogen oxides , lead, sulfur and other particulates, for that we need the effort to reduce pollution caused by exhausted emissions through optimal combustion in chamber. This study aims to determine the thickness of the shim to pressure, device for spraying diesel on an injector. It influences motor burning process and trace generated fog and to determine the shim thickness used for nozzle Type Bosch No. DN12SD12T. In this paper the authors collected data using methods of literature, interview, observation and experiment.  The type of vehicle in this study is Isuzu Panther C223 Turbo Diesel by using Nozzle Type One Hole and it has nozzle serial number Type Bosch No. DN12SD12T. The result showed that the opening pressure for standart nozzles is Type Bosch No. DN12SD12T for 5 times experiment for the shim thickness of 0.05 mm to produce an injection pressure of 5 bar, shim thickness of 0.10 mm to produce an injection pressure of 10 bar, shim thickness of 0.15 mm to produce an injection pressure of 15 bar, shim thickness 0, 20 mm to produce an injection pressure of 20 bar, shim thickness of 0.25 mm to produce an injection pressure of 25 bar, the shim thickness selected from 0.05 mm to 0.25 mm with carburetion pressure of 25 bar. The thicker the shim setter given the opening pressure nozzles and pressure also getting bigger. The thicker the shim setter, the bigger the force that is received by a spring on the nozzle.